Effects of multiple drivers of ocean global change on the physiology and functional gene expression of the coccolithophore Emiliania huxleyi - Feng, Y; Roleda, MY; Armstrong, E; Summerfield, TC; Law, CS; Hurd, CL; Boyd, PW (Global Change Biology, 2020)
Ongoing ocean global change due to anthropogenic activities is causing multiple chemical and physical seawater properties to change simultaneously, which may affect the physiology of marine phytoplankton. The coccolithophore Emiliania huxleyi is a model species often employed in the study of the marine carbon cycle. The effect of ocean acidification (OA) on coccolithophore calcification has been extensively studied; however, physiological responses to multiple environmental drivers are still largely unknown. Here we examined two‐way and multiple driver effects of OA and other key environmental driversnitrate, phosphate, irradiance, and temperatureon the growth, photosynthetic, and calcification rates, and the elemental composition of E. huxleyi . In addition, changes in functional gene expression were examined to understand the molecular mechanisms underpinning the physiological responses. The single driver manipulation experiments suggest decreased nitrate supply being the most important driver regulating E. huxleyi physiology, by significantly reducing the growth, photosynthetic, and calcification rates. In addition, the interaction of OA and decreased nitrate supply (projected for year 2100) had more negative synergistic effects on E. huxleyi physiology than all other two‐way factorial manipulations, suggesting a linkage between the single dominant driver (nitrate) effects and interactive effects with other drivers. Simultaneous manipulation of all five environmental drivers to the conditions of the projected year 2100 had the largest negative effects on most of the physiological metrics. Furthermore, functional genes associated with inorganic carbon acquisition ( RubisCO , AEL1 , and δCA ) and calcification ( CAX3 , AEL1 , PATP , and NhaA2 ) were most downregulated by the multiple driver manipulation, revealing linkages between responses of functional gene expression and associated physiological metrics. These findings together indicate that for more holistic projections of coccolithophore responses to future ocean global change, it is necessary to understand the relative importance of environmental drivers both individually (i.e., mechanistic understanding) and interactively (i.e., cumulative effect) on coccolithophore physiology.